2018
DOI: 10.1038/nm.4463
|View full text |Cite
|
Sign up to set email alerts
|

Diverse genetic-driven immune landscapes dictate tumor progression through distinct mechanisms

Abstract: Multiple immune-cell types can infiltrate tumors and promote progression and metastasis through different mechanisms, including immunosuppression. How distinct genetic alterations in tumors affect the composition of the immune landscape is currently unclear. Here, we characterized the immune-cell composition of prostate cancers driven by the loss of the critical tumor suppressor gene Pten, either alone or in combination with the loss of Trp53, Zbtb7a or Pml. We observed a striking quantitative and qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
117
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(131 citation statements)
references
References 63 publications
8
117
0
Order By: Relevance
“…Consistent with and extending upon the iTRAQ proteomics outcome, literature search revealed that half of the top 50 upregulated genes in Pten ‐KO prostate tumors were associated with immunity and/or inflammation. These transcriptomic features plus the proteomic overexpression patterns corroborated the observed organ‐localized endogenous expansion within the Pten ‐KO prostate tumors of Gr‐1+CD11b+ MDSC, neutrophils, and other myeloid lineage monocytes reported by the Hong Wu laboratory 21 and confirmed by others 22,23 …”
Section: Resultssupporting
confidence: 79%
“…Consistent with and extending upon the iTRAQ proteomics outcome, literature search revealed that half of the top 50 upregulated genes in Pten ‐KO prostate tumors were associated with immunity and/or inflammation. These transcriptomic features plus the proteomic overexpression patterns corroborated the observed organ‐localized endogenous expansion within the Pten ‐KO prostate tumors of Gr‐1+CD11b+ MDSC, neutrophils, and other myeloid lineage monocytes reported by the Hong Wu laboratory 21 and confirmed by others 22,23 …”
Section: Resultssupporting
confidence: 79%
“…Therefore, we exploited RNA-seq data and additionally performed Nanostring analysis of 700 immune-related genes on tissues from tumor-bearing mice treated for 7 and 14 consecutive days with MEKi ( Figures S3A-C ). Through interrogation of gene signatures indicative of different myeloid cell types (7,23,24) ( Supplementary Table 2 ), we found a statistically significant reduction in the level of signatures driven by tumor associated macrophages (TAM) (23) (Figure 3A and 3B ) both at 1 and 2 weeks of MEKi, while one week of MEKi was associated with elevated expression of genes related to PMN (polymorphonuclear leukocytes) ( Figure 3A and 3B ). Consistently, genes related to macrophage recruitment ( Ccl2, Cxcl3 ), macrophage differentiation ( Csf3, Cxcl12 ) or macrophage immunosuppressive activity ( Mrc1, Ccl17 and Ccl22 ) were among the most downregulated genes in MEKi treated tumors either at one week or two weeks of treatment ( Figure 3C and 3D ).…”
Section: Resultsmentioning
confidence: 99%
“…It was also suggested that PTEN loss causes prostate cancer initiation and progression by upregulation of inflammatory and cytokine-cytokine receptor signaling pathways and these associate with marked chronic and extensive MDSCs immune cell infiltration [27]. Comparative analysis of prostate cancer models showed that the diverse genetics of prostate cancer with PTEN loss can directly determine the differential infiltration and composition of immune cells in the TME [39]. Major tumor drivers can activate proinflammatory and immunosuppressive programs and at gene-specific intrinsic pathways are at the core of diverse protumoral immune-cell recruitment and infiltration [39].…”
Section: Evidences For Immunosuppressive Tumour Microenvironment In Pmentioning
confidence: 99%
“…Comparative analysis of prostate cancer models showed that the diverse genetics of prostate cancer with PTEN loss can directly determine the differential infiltration and composition of immune cells in the TME [39]. Major tumor drivers can activate proinflammatory and immunosuppressive programs and at gene-specific intrinsic pathways are at the core of diverse protumoral immune-cell recruitment and infiltration [39].…”
Section: Evidences For Immunosuppressive Tumour Microenvironment In Pmentioning
confidence: 99%